Modelling Coronary Heart Disease Mortality declines in the Republic of Ireland, 1985-2006 - BENNETT, KATHLEEN (My University, 2013)
BACKGROUND: Consistent declines in coronary heart disease (CHD) death rates have been previously observed in Ireland since 1985. AIMS & METHODS: To use the previously validated Irish IMPACT CHD mortality model to further examine the subsequent CHD mortality falls from 1985 through to 2006, and to determine the contribution of risk factor changes and "evidence based" treatments to this decline by age and gender. RESULTS: CHD mortality rates fell by 68% in men (63% in 65-84 years) and by 69% in women (66% in 65-84 years). This resulted in approximately 6450 fewer CHD deaths than if mortality rates had not changed. Overall, approximately 40% (38% in men; 45% in women) of the CHD mortality decline could be attributed to improvements in treatment uptake, particularly secondary prevention (12%), angina (9%), and heart failure therapies (8%). Approximately 48% of the CHD mortality decline was attributable to risk factor improvements (54% in men; 37% in women); the biggest contributions came from falls in population systolic pressure (28%), cholesterol (24%), and physical inactivity levels (10%). Negative trends in diabetes and obesity levels generated an estimated 17% additional CHD deaths. The largest benefits from improvements in risk factors were seen in men aged 25-64 years, while the greatest treatment benefits occurred in women aged 65-84 years. The model explained approximately 88% of the observed mortality declines. CONCLUSION: Falls in CHD mortality have continued in both sexes in Ireland, but with notable gender and age differences. The continued increase in diabetes and obesity levels is particularly worrying.
PUBLISHED
Keywords: Coronary heart disease